Short to mid-term effects of transrenal fixation of aortic stent grafts on renal function: A systematic review - Sun, Zhonghua; Stevenson, G. (Radiological Society of North America, 2006)
Purpose: To perform a systematic review of short to mid-term effects of the transrenal fixation of aortic stent grafts on renal function in patients with abdominal aortic aneurysms.Materials and Methods: A search of PubMed, MEDLINE and EMABSE databases for English literature was performed. Studies with at least 10 patients were included in the data analysis. Only studies dealing with transrenal fixation of aortic stent grafts and follow-up of renal function were included in the review. A log-linear model was used to meta-analyse these studies comparing transrenal and infrarenal fixation.Results: A total of 22 studies were found to meet the criteria and 21 were included for analysis; as two studies dealt with the same group of patients and one was excluded. Comparison of transrenal fixation with infrarenal fixation was found in seven studies. The odds ratio (and 95% confidence limits and p value) of transrenal/infrarenal fixation was only found to be statistically significant in postprocedural renal infarction (combined odds ratio: 5.189, 95% CI: 3.198, 8.420, p<0.001). No significant difference was found for transrenal/infrarenal fixation in renal dysfunction, renal artery occlusion or endoleaks (p>0.05).Conclusion: Our review showed that transrenal fixation of aortic stent grafts seems to be a relatively safe alternative when compared to infrarenal fixation in terms of short to mid-term follow-up. However, postprocedural renal infarction was significantly higher in transrenal fixation.